Development of Smart Kids Worksheet Teaching Materials on Pancasila Materials Based on Local Wisdom - Ambar Isnawati; Linda Astriani (Indonesian Journal of Primary Education, 2022)
This study aims to develop teaching materials for smart kids worksheets on Pancasila based on local wisdom. This research is motivated by the lack of teaching materials in understanding Civics subjects on Pancasila material The method used is the Research and Development (RD) method using the Analysis, Design, Development, Implementation, Evaluation (ADDIE) model. The subjects in the study were grade 2 students at SD Negeri 1 Cisantana, Cigugur District, Kuningan Regency. The results showed that the smart kids worksheet teaching materials were very valid based on the calculation results of linguists with an average score of 90%, material experts with an average score of 92%, and media experts with an average score of 94%. The results of the practicality test of teachers obtained an average of 93.3%, and the results of trials carried out in small groups obtained 96.6% and in large group trials obtained a score of 95%, this indicates a high level of practicality in both groups. The results showed that the worksheet smart kids teaching materials developed with the ADDIE model were valid and practical to be applied to Civics learning.